Effects of Economic Deterrence Theory and Environmental Regulation on Tax Evasion: Evidence from Energy Sector - Ya'u, Abba; Miraz, Mahadi Hasan; Saad, Natrah; Bala, Hussaini; Rangasamy, Dhanuskodi; Olaniyi, Oladokun Nafi’u; Mustapha, Umar Aliyu (International Journal of Energy Economics and Policy, 2023)
Environmental regulation is the responsibility of individuals, corporations, and other entities to prevent environmental damage or improve the tarnished environment. The Environmental law of every country works to protect the natural resources of land, water, air, and soil. There are research evidence that environmental regulation influences Corporate taxes. Economic deterrence theory acted as deterrent to threats of punishment for unwanted or illegal behavior. The fundamental concept of the theory is deterring the taxpayers into compliance by the risk of audit, penalty, etc. The objective of the study is to analyze the impact of economic deterrence theory and environmental regulation on corporate tax evasion, particularly petroleum profit taxes in Nigeria. The components of Economic deterrence theory (tax agents, tax complexity, tax knowledge) and environmental regulations are the independent variables and corporate tax evasion particularly PPT is the dependent variable of the study. It is quantitative research based on primary data which was collected from the oil and gas companies’ representatives. Structural Equation Modelling techniques were applied, and the outcome of the research is a positive and significant relationship between tax agents, tax complexity, tax knowledge, and environmental regulations on corporate tax evasion. The result further shows a positive but non-significant relationship between tax audits and perceived petroleum profit tax evasion. The study draws the attention of policymakers to formulate environmental regulations that are more robust, simple, and flexible, to reduce adverse effects of environmental damage on the economic growth and development of oil and gas-producing countries.